Comparisons Between Frontline Therapy and a Combination of Eltrombopag Plus Immunosuppression Therapy and Human Leukocyte Antigen-Haploidentical Hematopoietic Stem Cell Transplantation in Patients With Severe Aplastic Anemia: A Systematic Review - Yang, Yuan; Ji, Jiang; Tang, Zengwei; Han, Bing (Frontiers in Oncology, 2021)
Background and Aims: This study aimed at comparing the efficacy and safety of eltrombopag (EPAG) plus immunosuppressive therapies (ISTs) and haploidentical hematopoietic stem cell transplantation (haplo-HSCT) in the frontline treatment for severe aplastic anemia (SAA) patients. Methods: Four electronic databases and Clinicaltrials.gov were comprehensively searched from January 2010 to August 2020. Studies that aimed at evaluating the efficacy and safety of EPAG+IST or haplo-HSCT in SAA patients were included. One-/2-year overall survival (OS), complete response (CR), and overall response rates (ORRs) were indirectly compared between EPAG+IST and haplo-HSCT. Results: A total of 447 patients involved in 10 cohort studies were found to be eligible for this study. A narrative synthesis was performed due to lack of data directly comparing the outcome of EPAG+IST and haplo-HSCT. Consistent with the analysis results in the whole population, subgroup analyses in the age-matched population showed that there was no significant difference in ORR between EPAG+IST and haplo-HSCT groups. However, the CR rate was lower in the EPAG+IST group when compared with the haplo-HSCT group. The incidence rate of clonal evolution/SAA relapse ranged at 8–14 and 19–31% in the EPAG+IST group but not reported in the haplo-HSCT group. The incidence rate for acute graft vs. host disease (aGVHD) and chronic graft vs. host disease (cGVHD) ranged at 52–57 and 12–67%, respectively, for the haplo-HSCT group. The main causes of deaths were infections in the EPAG+IST group, and GVHD and infections in the haplo-HSCT group. Conclusion: EPAG+IST has a comparable ORR and 1-/2-year OS but lower CR rate when indirectly compared with haplo-HSCT in the frontline treatment of patients with SAA. Patients treated with haplo-HSCT may exhibit a high incidence of GVHD, whereas patients treated with EPAG+IST may experience more relapses or clone evolution.